2011
DOI: 10.1007/s10815-011-9562-4
|View full text |Cite
|
Sign up to set email alerts
|

Fully-mature antral mouse oocytes are transcriptionally silent but their heterochromatin maintains a transcriptional permissive histone acetylation profile

Abstract: Purpose The final stages of antral mouse oocytes maturation are characterised by the transition from transcriptionally active NSN to inactive SN oocytes. Here, we studied the profile of histone acetylation changes occurring during the NSN-to-SN transition. Methods During the NSN-to-SN transition, oocytes were classified based on their chromatin organisation and the immunocytochemical profile of histones H2B, H3 and H4 acetylation was analysed. Results We described four patterns of immunostaining common to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In addition, the zygote also inherits from the egg other epigenetic mechanisms regulating gene expression, the best known of which are DNA methylation, histone modifications, and chromatin organization [42]. According to Zuccotti et al [43], maintenance of a favorable transcriptional epigenetic context in the heterochromatin of transcriptionally silent SN oocytes might be related to the early stages of development when transcripts from these heterochromatic regions are functional to preimplantation progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the zygote also inherits from the egg other epigenetic mechanisms regulating gene expression, the best known of which are DNA methylation, histone modifications, and chromatin organization [42]. According to Zuccotti et al [43], maintenance of a favorable transcriptional epigenetic context in the heterochromatin of transcriptionally silent SN oocytes might be related to the early stages of development when transcripts from these heterochromatic regions are functional to preimplantation progression.…”
Section: Discussionmentioning
confidence: 99%
“…Developing oocytes and early-stage embryos are transcriptionally quiescent in mouse, zebrafish, and C. elegans (Su et al, 2007; Xia et al, 2012; Zuccotti et al, 2011); thus post-transcriptional and translational regulation of gene expression is crucial for oocyte development and the oocyte-to-embryo transition. Both the RAS-ERK pathway and Dicer have been shown to regulate key steps in oogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to somatic nucleoli, active ribosomal genes have been described only at the NLB surface (Bouniol-Baly et al, 1999;Pesty et al, 2007). SN-oocytes have higher meiotic and developmental competence than NSN-oocytes and correspond to a more advanced stage of oocyte development (Zuccotti et al, 2002(Zuccotti et al, , 2011Inoue et al, 2008). Recent analysis of the global transcriptome profile in mouse NSN-and SN-oocytes showed that they are very similar but not identical: NSN-oocytes are enriched in methylated and acetylated peptides (Monti et al, 2013), whereas SN-oocytes are characterized by higher levels of methylation and acetylation of DNAs (Kageyama et al 2007).…”
Section: Introductionmentioning
confidence: 99%